Fuzzy Logic-based digital filtering for temperature measurement via K-type thermocouple - (:unkn) unknown (IEEE, 2003)
The performance of a controller designed by using any method depends on the analog quantity to be controlled how accurate and noiseless it is measured. lit this paper, the noise on the temperature data measured via a K-type thermocouple mounted on the lab set suitably realized for the purpose of measuring thermal expansion of metal samples is reduced by using two cascade band-pass filters (BPF) whose bandwidth can be set by taking advantage of Fuzzy Logic Controller's (FLC) relative error membership function.